Where local modernities meet: The Calouste Gulbenkian Foundation in Iraq, 1957-1973 - Agarez, R. C. (2022)
The Gulbenkian Hall on Tayeran Square in Baghdad - one of the few venues there where works of Iraqi modern art can be seen today - was designed and built between 1957 and 1962 by the Calouste Gulbenkian Foundation, aimed at supporting the city's budding modern arts scene with its first purpose-built gallery. Importantly, it was also intended as a demonstration of the foundation's seriousness of purposes in strengthening the cultural, educational, scientific and public health-related infrastructure of Iraq - a purpose to which the institution, established in Lisbon in 1956, had decided to channel part of its oil revenues, largely originated in the country. In the tightrope exercise of combining its own financial viability with its philanthropism, the Foundation thereby helped establishing the material and intellectual backbone of modern-day Iraq, through very diverse means. This exercise included approving around 250 'construction grants' in Iraq, 600 scholarships for graduate and post-graduate training, home and abroad, and material support ranging from library collections to television equipment. The operation peaked with al-Shaab Stadium in Baghdad (1957-1966), meant as a contribution for the advancement of Iraqi physical education. Focusing on the sports complex and arts centre initiatives as epitomes of post-colonial, soft-power diplomacy processes and products, this paper examines how the archive of a philanthropy in Portugal can shed light on the unseen history of ostensibly distant objects that, despite circumstances over the past three decades, have entered Iraqi collective memory as beacons of normality, while enquiring the ways by which seemingly unconnected cultures of modern built-environment production come into contact, yielding new, hybrid outputs.